Legal frameworks of transparency principle in the prosecutors activity of Ukraine - Piliai, Ivan (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
In the article, the author studies the concept of transparency of the prosecutor’s office of Ukraine. The author analyzes a legal regulation of awareness of the system and prosecutor’s functioning. Among other things, the author gives the definition of the following terminology: «principle of transparency» and «legal rules for the implementation of the transparency principle». The author proposes the changes to the current legislation in order to overcome conflicts and gaps in implementation of the transparency principle in the prosecutor’s activity.